2017
DOI: 10.1016/j.jad.2016.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between self-reported childhood traumatic experiences, attachment style, neuroticism and features of borderline personality disorders in patients with mood disorders

Abstract: We found moderately strong correlations between self-reported BPD features and concurrent high neuroticism, reported childhood traumatic experiences and Attachment Anxiety also among patients with mood disorders. Independent predictors for BPD features include young age, frequency of childhood traumatic experiences and high neuroticism. Insecure attachment may partially mediate the relationship between childhood traumatic experiences and borderline features among mood disorder patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 95 publications
2
42
0
Order By: Relevance
“…This finding is consistent with a large body of research conducted in adult samples that found a link between childhood maltreatment and an increased risk for maladaptive personality traits and personality pathology (Hengartner et al, 2015;Hock et al, 2018). In particular, traumatic childhood experiences are considered a significant predictor for borderline personality features in adolescents and adults (Baryshnikov et al, 2017;Lobbestael, Arntz, & Bernstein, 2010;Mosquera, Gonzalez, & Leeds, 2014). Our results add to existing literature, showing that more severe abuse and neglect increases the risk of developing pathological personality features in adults (Sharp & Fonagy, 2015) and adolescents (Sansone, Songer, & Miller, 2005).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This finding is consistent with a large body of research conducted in adult samples that found a link between childhood maltreatment and an increased risk for maladaptive personality traits and personality pathology (Hengartner et al, 2015;Hock et al, 2018). In particular, traumatic childhood experiences are considered a significant predictor for borderline personality features in adolescents and adults (Baryshnikov et al, 2017;Lobbestael, Arntz, & Bernstein, 2010;Mosquera, Gonzalez, & Leeds, 2014). Our results add to existing literature, showing that more severe abuse and neglect increases the risk of developing pathological personality features in adults (Sharp & Fonagy, 2015) and adolescents (Sansone, Songer, & Miller, 2005).…”
Section: Discussionsupporting
confidence: 92%
“…Current findings have demonstrated an exploratory link between childhood traumatic experiences and personality pathology (Baryshnikov et al, 2017;Fonagy, Target, & Gergely, 2000). However, the only studies showing a mediating effect of insecure attachment are limited to adult borderline PD (Baryshnikov et al, 2017;Godbout et al, 2019;Minzenberg, Poole, & Vinogradov, 2006), and they focus on attachment styles derived from self-report questionnaires of attachment which do not consider the unresolved attachment representation (Ravitz, Maunder, Hunter, Sthankiya, & Lancee, 2010). Given that the responsiveness and social proximity to attachment figures play a crucial role for affect regulation difficulties in individuals with personality pathology (Hengartner et al, 2015), impairments in their emotion regulation might become apparent in response to traumatic experiences, especially in those with an unresolved attachment pattern (Bizzi et al, 2015).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Regarding specific personality pathologies, childhood SLEs have been suggested to play a role in development of antisocial and borderline PD traits (Jaffee et al 2004; Afifi et al 2011; Hyde et al 2016; Baryshnikov et al 2017), although a biometric study reported that the association with borderline PD may be subject to unmeasured genetic confounding (Bornovalova et al 2013). These two DSM-IV PDs have been found to be associated with AUD even after adjusting for the other eight PDs (Long et al 2017).…”
Section: Introductionmentioning
confidence: 99%